Status Keberlanjutan Banggai Cardinalfish di kabupaten Banggai Laut - Hasim, Hasim; Hamzah, Sri Nuryatin; Sunani, Muh. Raziq Faruki H. (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
Banggai Islands-Central Sulawesi-Indonesia holds one of the endemic marine biodiversity, the Banggai Cardinalfish (Pterapogon kauderni). The Banggai Cardinalfish has been listed as Endangered on the IUCN (International Union for the Conservation of Nature) Red List since 2007, and the 17th CITES CoP in appendix II of CITES in 2016. There are two main threats to the species, namely utilisation as ornamental fish and habitat degradation. This study aims to determine the sustainability status of Banggai cardinalfish in Banggai Laut Regency. This research was conducted from January to March 2024 in three villages (Popisi Village, Tolisetubono Village and Bonebaru Village) in North Banggai District, Banggai Laut Regency, Central Sulawesi Province. This research uses descriptive qualitative methods, which uses primary and secondary data to assess the five dimensions of sustainability of Banggai Cardinalfish management: ecological, social, economic, policy and institutional dimensions and technology and infrastructure. Each data obtained will be scored to get the median value of each attribute. The scoring data obtained from each attribute was analysed with RAPFISH (Rapid Appraisal for Fisheries) to reflect the sustainability position with a scale score of 0% (poor) to 100% (good). The results showed that the multidimensional sustainability index of Banggai Cardinalfish management is 54.70 which means that the sustainability status of Banggai Cardinalfish management is quite sustainable, with the value of each dimension showing the value of ecology (70.05), social (64.12), economy (43.34), policy and institutions (36.92) and technology and infrastructure (58.06).